Allergy, Asthma & Clinical Immunology - Warrington, Richard
Allergy, Asthma & Clinical Immunology (AACI), the official journal of the Canadian Society of Allergy and Clinical Immunology (CSACI), is an open access journal that encompasses all aspects of diagnosis, epidemiology, prevention and treatment of allergic and immunologic disease. By offering a high-visibility forum for new insights and discussions, AACI provides a platform for the dissemination of allergy and clinical immunology research and reviews amongst allergists, pulmonologists, immunologists and other physicians, healthcare workers, medical students and the public worldwide. AACI reports on basic research and clinically applied studies in the following areas and other related topics: asthma and occupational lung disease, rhinoconjunctivitis and rhinosinusitis, drug hypersensitivity, allergic skin diseases, urticaria and angioedema, venom hypersensitivity, anaphylaxis and food allergy, immunotherapy, immune modulators and biologics, immune deficiency and autoimmunity, T cell and B cell functions, regulatory T cells, natural killer cells, mast cell and eosinophil functions, complement abnormalities.